2010
DOI: 10.3109/17483107.2010.495815
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study: influence of visual cue color on freezing of gait in persons with Parkinson's disease

Abstract: Purpose To investigate the effect of red and green light beams on gait and freezing of gait (FOG) in persons with Parkinson’s disease (PD). Methods Seven persons with PD who experienced FOG participated in the study. Gait and turning performances were studied while walking with canes with red, green, and no light beams while ‘off’ and ‘on’ anti-parkinsonian medications. Gait speed, cadence, and stride were recorded. Time and number of freezing episodes were recorded during a 50-foot walk and a 360° turn. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(73 citation statements)
references
References 21 publications
(32 reference statements)
2
71
0
Order By: Relevance
“…Hence, cognitive impairment can make a major contribution to the degree of colour discrimination deficits in PD [ 48 ]. In addition, the effect of coloured lights on gait and freezing of gait have been investigated in PD, with in a pilot experiment, green light improving gait and attenuating freezing of gait better than red or no light [ 49 ].…”
Section: Oculo-visual Symptoms In Pdmentioning
confidence: 99%
“…Hence, cognitive impairment can make a major contribution to the degree of colour discrimination deficits in PD [ 48 ]. In addition, the effect of coloured lights on gait and freezing of gait have been investigated in PD, with in a pilot experiment, green light improving gait and attenuating freezing of gait better than red or no light [ 49 ].…”
Section: Oculo-visual Symptoms In Pdmentioning
confidence: 99%
“…These studies can be grouped into two categories. Immediate cueing: the majority of studies have investigated the immediate effect of cueing on FoG [36,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59]. These studies predominantly evaluated the effect of cueing over a single session of use, with the objective of the cueing being to provide an immediate benefit in terms a reduction in the number/duration of FoG episodes.Therapeutic cueing: a number of studies have investigated the therapeutic effect of cueing [60,61,62,63,64,65,66,67,68,69,70].…”
Section: Introductionmentioning
confidence: 99%
“…So far, research into specific physiotherapeutic methods to alleviate FOG during turning has suggested that cueing 18,21,22 can reduce FOG. Cueing is defined as "applying temporal or spatial stimuli associated with the initiation and ongoing facilitation of motor activity" 23 .…”
Section: Introductionmentioning
confidence: 99%